2023
DOI: 10.1186/s13018-023-04446-5
|View full text |Cite
|
Sign up to set email alerts
|

AI algorithms for accurate prediction of osteoporotic fractures in patients with diabetes: an up-to-date review

Zeting Li,
Wen Zhao,
Xiahong Lin
et al.

Abstract: Osteoporotic fractures impose a substantial burden on patients with diabetes due to their unique characteristics in bone metabolism, limiting the efficacy of conventional fracture prediction tools. Artificial intelligence (AI) algorithms have shown great promise in predicting osteoporotic fractures. This review aims to evaluate the application of traditional fracture prediction tools (FRAX, QFracture, and Garvan FRC) in patients with diabetes and osteoporosis, review AI-based fracture prediction achievements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Osteoporosis with bone loss as a complication of diabetes has attracted clinical attention as an intractable disease [24,25]. Streptozotocin (STZ) is used as a model animal for diabetes because it destroys the pancreas and induces type 1 diabetes due to impaired insulin secretion [26].…”
Section: Involvement Of S Horneri Water Extract Component In Osteopor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporosis with bone loss as a complication of diabetes has attracted clinical attention as an intractable disease [24,25]. Streptozotocin (STZ) is used as a model animal for diabetes because it destroys the pancreas and induces type 1 diabetes due to impaired insulin secretion [26].…”
Section: Involvement Of S Horneri Water Extract Component In Osteopor...mentioning
confidence: 99%
“…Specifically, Formax OT was found to significantly reduce tartrate-resistant acid phosphatase, a serum marker of bone resorption, and suppress bone resorption (bone mineral dissolution) [24]. It was concluded that S. horneri extract constituents exert their bone resorption inhibiting effect early in the intake and then promote bone formation, thus helping to maintain bone mass.…”
Section: Complementary Effects Of S Horneri Water Extract Component I...mentioning
confidence: 99%